2022
DOI: 10.1111/iju.14926
|View full text |Cite
|
Sign up to set email alerts
|

Single immediate instillation of chemotherapy is associated with decreased recurrence and progression in patients with high‐risk non‐muscle‐invasive bladder cancer who receive adjuvant induction bacillus Calmette‐Guérin therapy

Abstract: Abbreviations & Acronyms AE = adverse event BC = bladder cancer BCG = bacillus Calmette-Gu erin CI = confidence interval CIS = carcinoma in situ CT = computed tomography ECOG PS = Eastern Cooperative Oncology Group performance status EPI = epirubicin GEM = gemcitabine HR = hazard ratio IPTW = inverse probability of treatment weighting IQR = interquartile range MIBC = muscle-invasive bladder cancer NMIBC = non-muscleinvasive bladder cancer RFS = recurrence-free survival SHR = subdistribution hazard ratio THP = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…These costs reflected the long-term survival and associated need for lifelong routine monitoring in patients with bladder cancer. Overall, bladder cancer was the fifth most expensive cancer in the US in terms of total medical expenditure, with direct annual costs of USD 3.7 billion in 2001 values (74). These findings were confirmed in a 2014 review that reviewed costs over the bladder cancer diagnosis, treatment, and surveillance trajectory (75).…”
Section: Economic Burden Of Nmibcmentioning
confidence: 85%
See 1 more Smart Citation
“…These costs reflected the long-term survival and associated need for lifelong routine monitoring in patients with bladder cancer. Overall, bladder cancer was the fifth most expensive cancer in the US in terms of total medical expenditure, with direct annual costs of USD 3.7 billion in 2001 values (74). These findings were confirmed in a 2014 review that reviewed costs over the bladder cancer diagnosis, treatment, and surveillance trajectory (75).…”
Section: Economic Burden Of Nmibcmentioning
confidence: 85%
“…Assessment of the economic burden of bladder cancer dates back at least to a 2003 health economic review (74). This review of forty-four studies concluded that bladder cancer was associated with the highest per-patient cost of all cancers from diagnosis to death, with, at the time, costs of USD 96,000 to USD 187,000 (2001 values).…”
Section: Economic Burden Of Nmibcmentioning
confidence: 99%